Screening for cerebral amyloid angiopathy based on serological biomarkers analysis using a dielectrophoretic force-driven biosensor platform. Issue 23 (1st November 2021) - Kim, Hye Jin; Park, Dongsung; Yun, Gyihyaon; Kim, Hongrae; Kim, Hyug-Gi; Lee, Kyung Mi; Hong, Il Ki; Park, Key-Chung; Lee, Jin San; Hwang, Kyo Seon
Abstract : Screening of cerebral amyloid angiopathy and Alzheimer's disease by analyzing plasma amyloid-β using a highly sensitive dielectrophoretic force-driven biosensor platform. Abstract : We aimed to analyze plasma amyloid-β (Aβ)1–40 and Aβ1–42 using a highly sensitive dielectrophoretic-driven biosensor platform to demonstrate the possibility of precise cerebral amyloid angiopathy (CAA) diagnosis in participants classified according to Aβ-positron emission tomography (PET) positivity and the neuroimaging criteria for CAA. We prospectively recruited 25 people with non-Alzheimer's disease (non-AD) and 19 patients with Alzheimer's disease (AD), which were further classified into the CAA− and CAA+ (possible and probable CAA) groups according to the modified Boston criteria. Patients underwent plasma Aβ analysis using a highly sensitive nano-biosensor platform, Aβ-PET scanning, and detailed neuropsychological testing. As a result, the average signal levels of Aβ1–42/1–40 differed significantly between the non-AD and AD groups, and the CAA+ group exhibited significantly higher Aβ1–40 signal levels than the CAA− group in both non-AD and AD groups. The concordance between the Aβ1–40 signal level and the neuroimaging criteria for CAA was nearly perfect, with areas under the curve of 0.954 (95% confidence interval (CI) 0.856–1.000), 0.969 (0.894–1.000), 0.867 (0.648–1.000), and 1.000 (1.000–1.000) in the non-AD/CAA− vs. non-AD/possible CAA, non-AD/CAA− vs. non-AD/probable CAA, AD/CAA− vs. AD/possible CAA, and AD/CAA− vs. AD/probable CAA groups, respectively. Higher Aβ1–40 signal levels were significantly associated with the presence of CAA according to regression analyses, and the neuroimaging pattern analysis partly supported this result. Our findings suggest that measuring plasma Aβ1–40 signal levels using a highly sensitive biosensor platform could be a useful non-invasive CAA diagnostic method.